An Adjunctive Multi‐family Group Intervention with or without Patient Participation during an Inpatient Treatment for Adolescents with an Eating Disorder: A Pilot Study. (29th September 2017) - Depestele, Lies; Claes, Laurence; Dierckx, Eva; Colman, Roos; Schoevaerts, Katrien; Lemmens, Gilbert M.D.
Abstract: This study reports on a pilot study of a family group intervention with or without patient participation adjunctive to a specialized inpatient treatment for eating disorders (EDs). Participants were 112 female adolescent ED inpatients and one or both of their parents. The parents were invited to participate in an adjunctive multi‐family group with patient (MFT) or in a similar multi‐parent group without patient participation (MPT). Questionnaires assessing ED symptoms, family functioning and caregiving experiences were administered before and after intervention. Post‐intervention results obtained from both patient and parent(s) indicated that improvement in ED symptoms and parental burden occurred after both types of interventions. Family functioning improved differently according to the informant: fathers reported an improvement of general family functioning, patients reported an improvement of problem solving and mothers reported a decrease in problem solving across both formats. This study emphasized the importance of including a multi‐informant approach in family interventions. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.